Computation in biological systems as a quantum mechanical simulation. (April 2022) - Cottam, Ron; Vounckx, Roger
Abstract: Our initial premise is that computation as we know it is formally derived from our bodies' internal processing, via our neural processors. Going backwards in time, our bodies' internal processing is in turn derived from wider Nature's own style of processing, which in turn is a rendition of the Universe's processing following the Big Bang. Computation is described as consisting of two intimately connected parts: comparative processing and conclusive processing. Our examination of post-Big Bang processing, biological processing, neural processing and human thinking supports our initial premise and the conclusion that computation is the motor for evolutionary emergence across the entire timescale of the Universe.